Diversifying Cropping for Sustainable Farming: Challenges and Opportunities in Bangladesh - Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2025)
Agriculture in Bangladesh is predominantly focused on rice, with approximately 75% of arable land dedicated to its cultivation. Farmers in the country cultivate rice up to three times a year, with the rice-rice cropping pattern covering about 27% of the country’s agricultural area. In certain regions, particularly in Northern Bangladesh, this figure can reach as high as 60% (Nasim et al. 2018).